2004
DOI: 10.1101/gr.2972804
|View full text |Cite
|
Sign up to set email alerts
|

Coelacanth genome sequence reveals the evolutionary history of vertebrate genes

Abstract: The coelacanth is one of the nearest living relatives of tetrapods. However, a teleost species such as zebrafish or Fugu is typically used as the outgroup in current tetrapod comparative sequence analyses. Such studies are complicated by the fact that teleost genomes have undergone a whole-genome duplication event, as well as individual gene-duplication events. Here, we demonstrate the value of coelacanth genome sequence by complete sequencing and analysis of the protocadherin gene cluster of the Indonesian co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
76
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(82 citation statements)
references
References 32 publications
6
76
0
Order By: Relevance
“…In addition, the likelihood-ratio test confirmed that the branch length for coelacanths is significantly shorter than those of the three other vertebrates (P < 0.01; Supplemental Information 6.1). Our data provide genome-wide confirmation of previous studies that used a small number of selected gene sets (Noonan et al 2004;Amemiya et al 2010;Higasa et al 2012).…”
Section: Estimation Of the Substitution Ratesupporting
confidence: 78%
See 1 more Smart Citation
“…In addition, the likelihood-ratio test confirmed that the branch length for coelacanths is significantly shorter than those of the three other vertebrates (P < 0.01; Supplemental Information 6.1). Our data provide genome-wide confirmation of previous studies that used a small number of selected gene sets (Noonan et al 2004;Amemiya et al 2010;Higasa et al 2012).…”
Section: Estimation Of the Substitution Ratesupporting
confidence: 78%
“…The evolutionary rate of the coelacanth genome has been debated for many years (Noonan et al 2004;Amemiya et al 2010;Higasa et al 2012). With the entire genome available, we first compared a set of 5247 orthologous genes for coelacanth and four other vertebrates-human, chicken, frog, and zebrafish-and then constructed a maximum-likelihood tree to evaluate the difference in evolutionary rates among vertebrates (Fig.…”
Section: Estimation Of the Substitution Ratementioning
confidence: 99%
“…An additional whole genome duplication may have occurred in the teleost lineage after its split from the tetrapod lineage, from which only a subset has been retained in modern teleost genomes [64]. Coelacanth, that is considered a close relative to tetrapods, however shows no evidence for whole genome duplication [65]. It is interesting that after whole genome duplication events, nonchemosensory GPCR genes were retained with a higher probability than expected [66].…”
Section: Gpcr Repertoiresmentioning
confidence: 94%
“…It is composed of tandem arrays of paralogous genes that are highly susceptible to lineage-specific gene losses, tandem duplications, and gene conversion (2)(3)(4)(5)(6)(7). These clustered genes are distinct from nonclustered protocadherin genes by possessing a large coding exon that codes for the entire extracellular domain, the transmembrane domain, and a small portion of the cytoplasmic domain, whereas the extracellular domain of the nonclustered protocadherins is usually encoded by multiple exons (8).…”
mentioning
confidence: 99%